Plasma concentrations of buprenorphine administered via matrix-type transdermal patches applied at three different anatomical locations in healthy adult horses - Paranjape, Vaidehi V.; Knych, Heather K.; Berghaus, Londa J.; Giancola, Shyla; Cathcart, Jessica; Reed, Rachel A. (Frontiers in Pain Research, 2024)
BackgroundAnatomical location-dependent differences in transdermal opioid penetration are well described in human patients. Although this has been investigated in horses with fentanyl, there is no literature available on location-dependent plasma buprenorphine concentrations when administered as a transdermal matrix-type patch.ObjectiveThis study aims to compare the plasma concentrations achieved from the matrix-type transdermal buprenorphine patches placed at different anatomical sites (metacarpus, gaskin, and ventral tail base) in healthy adult horses.Study designThis is a randomized experimental study with a Latin square design.MethodsSix adult horses were given each of three treatments with a minimum 10-day washout period. For each treatment, two 20 μg h−1 matrix-type buprenorphine patches were applied to the ventral aspect of the tail base (TailTDP), metacarpus region (MetacarpusTDP), or gaskin region (GaskinTDP). Whole blood samples (for determination of buprenorphine concentration) and physiological variables were collected before (0 h) and at 0.5, 2, 4, 6, 8, 10, 12, 16, 24, 32, 48, 56, 72, 96 and 120 h after patches were applied. The patches were removed 96 h following placement and were analyzed for residual buprenorphine content. Buprenorphine concentrations were measured in plasma by LC-MS/MS. A mixed-effects model was used to analyze the physiological variables.ResultsBetween the three treatment groups, there was no change in physiological variables across timepoints as compared to baseline and when compared to each other in a single horse and between horses (p > 0.3). When comparing all three locations, the buprenorphine uptake was observed to be more consistent with respect to measurable plasma concentrations >0.1 ng ml−1 when applied to the ventral aspect of the tail base. In the TailTDP group, the mean plasma buprenorphine concentrations were >0.1 ng ml−1 from 2 to 32 h. The highest group mean was 0.25 ng ml−1 noted at 4 h.ConclusionsThe metacarpal and gaskin regions presented more erratic and inconsistent buprenorphine uptake and plasma concentrations as compared to the ventral aspect of the tail base. Further research must be directed at investigating the optimal dose, achievable duration of analgesia, change in measurable plasma concentrations, and behavioral and systemic effects.